2019
DOI: 10.1002/cssc.201900779
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Electrochemical Reaction Pathways of CO2 Reduction to CN Species at S‐Vacancies of MoS2

Abstract: Although C1 species such as CO and CH4 constitute the majority of CO2 reduction (CO2 R) products on known catalysts, recent experiments showed that 1‐propanol with two C−C bonds is produced as the main CO2 R product on MoS2 single crystals in aqueous electrolytes. Herein, the CO2 R mechanism on MoS2 is investigated by using first‐principle calculations. Focusing on S‐vacancies (VS) as the catalytic site, potential free‐energy pathways to various CO2 R products are obtained by means of a computational hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
(122 reference statements)
0
22
0
Order By: Relevance
“…Although the smooth surfaces of the MoS 2 are proved to be catalytically inert, [36] hence the active sites may be at the basal planes, not the edges. In this regard, Kang et al [37] . used the first principle (ab initio) calculations to study the CO 2 electroreduction into C 2+ and higher hydrocarbons mechanisms on basal planes of MoS 2 .…”
Section: Catalysts For Co2 Conversion Into C3+ Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the smooth surfaces of the MoS 2 are proved to be catalytically inert, [36] hence the active sites may be at the basal planes, not the edges. In this regard, Kang et al [37] . used the first principle (ab initio) calculations to study the CO 2 electroreduction into C 2+ and higher hydrocarbons mechanisms on basal planes of MoS 2 .…”
Section: Catalysts For Co2 Conversion Into C3+ Productsmentioning
confidence: 99%
“…The sulfur‐vacancies of MoS 2 (V s ) can be produced in a 10% fraction during the MoS 2 film fabrications. These V s are considered to be the active sites for the hydrogen evolution reaction (HER) [37] . The study showed that bowl shape V s are the active sites for the formaldehyde intermediate, which is the key to forming a multi‐carbon product formed at the first protonation step.…”
Section: Catalysts For Co2 Conversion Into C3+ Productsmentioning
confidence: 99%
“…Besides transition metals, a variety of materials such as transition metal dichalcogenides, [9][10][11] nickel sulfides, [12] and single-atom-doped carbons [13][14][15][16][17][18][19][20][21][22][23][24][25] are attracting recent attentions as potential heterogeneous catalysts, especially for CO 2 R. In particular, transition metal-and nitrogen-codoped graphene (referred to as MÀ NÀ G, where M is a transition metal) has emerged as an important type of single-atom CO 2 R catalysts that produce CO with a remarkable activity and efficiency. For example, Ju et al discovered that MÀ NÀ G catalysts (M=Mn, Fe, Co, Ni, and Cu) selectively converts CO 2 into CO with small onset potentials (> À 0.3 V vs. RHE) and high faradaic efficiencies (FEs; > 60 % in the case of M=Fe and Ni).…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 is a 2 D material of increasing research interest recently owing to its interesting physical and electronic properties, including high conductivity, high surface area, and active sites for a diversity of applications . Previous reports relevant to Li–S batteries have used MoS 2 as a means to inhibit or anchor PS species during electrochemical cycling .…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] MoS 2 is a2Dm aterialo fi ncreasing research interest recently owing to itsi nterestingp hysical and electronic properties, including high conductivity,h ighs urfacea rea, and active sites for ad iversity of applications. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Previous reports relevant to Li-S batteries have used MoS 2 as am eans to inhibit or anchor PS speciesduring electrochemical cycling. [29] These can be generalized into three strategies using MoS 2 :p rotection by augmenting the separator,t he Li-metala node, and PS trapping by inclusion in ac omposite cathode.…”
Section: Introductionmentioning
confidence: 99%